Embarkasi dan Debarkasi Penumpang Kapal KM. GUNUNG DEMPO - Tata Rahmaningtyas; Dwi Antoro; Romanda Amrullah (Politeknik Ilmu Pelayaran Semarang, 2020)
This study aims to determine what factors can cause ship delays, and how to reduce them. The type of observation used is descriptive qualitative. This observation takes place at the Port of Anging Mamiri Makassar. Sources of data obtained from sources (informants), events or activities, documents and archives. The results showed that the cause of the delay in ship departure could be in the form of erratic weather factors, disorderly delivery, visitors, hawkers and baggage workers in the embarkation and debarkation of passengers, as well as engine damage. Efforts made to reduce delays are to always carry out routine checks on ship engines, always inquire and check the weather conditions at the next port port, and do not allow deliveries, visitors, hawkers and baggage workers to get on board.